An independent review and summary of geotechnical information pertaining to the sidewall stability of the Kimberley "Big Hole" mine, with specific focus on the weathering and deterioration of the Kimberley shales. - Maree, Wilmar (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.